Navigating the Progress and Future Directions of TikTok Research in the Innovative Era: A Bibliometric Analysis - Hasbullah, Nornajihah Nadia; Roni, Mastura; Hasan, Wan Hasmat Wan; Abidin, Mohd Isham; Husain, Nor Azmawati (Journal of Ecohumanism, 2025)
TikTok is an exponentially growing mobile video platform that has millions of global subscribers. Accordingly, more scientific and empirical studies from various fields have explored the platform. This study examined TikTok using a bibliometric approach, as TikTok studies using bibliometric and network analyses are scarce. This study bridged the research gap by examining the TikTok dynamic expansion from 2019 to 2023 using comprehensive bibliometric and network analysis. The Scopus database yielded 727 articles published in 169 journals, which were analysed using VOSviewer. The analysis highlighted key contributions on the evolution of publications, journals with the most publications, the most productive countries, keyword analysis, and the top three TikTok-related research hotspots. Among the 80 countries examined, the United States, Australia, and China revealed the highest number of publications on TikTok. The journal with the highest h-index was Social Media and Society, while the Journal of Medical Internet Research denoted the highest CiteScore. A cluster analysis of 2238 author keywords determined that the top three TikTok research tiers were related to computer science, arts and humanities, and business management. The analysis also emphasised the number of studies on TikTok. The significant implications for the prospective audience refined the research contribution. This study presented novel contributions to the literature by providing concrete evidence of current TikTok use.